1976
DOI: 10.1159/000175698
|View full text |Cite
|
Sign up to set email alerts
|

Schedule of Protein Ingestion and Circadian Rhythm of Certain Hepatic Enzyme Activities Involved in Glucose Metabolism in the Rat

Abstract: The circadian rhythms of liver glycogen, plasma glucose, corticosterone and insulin, and hepatic activity of PK, G6PDH, ME, Ac.CoA carbox. PEP-CK and GPT were studied in adult rats. Animals either received a mixed diet ad libitum (8 % protein) or a protein meal (1.1 g protein) given at 05:00 or 17:00 h, with free access to a protein-free diet (separately fed). When the protein meal was ingested during the lighted period (17:00) the 24-hour average level of liver PEP-CK was greater than in rats consuming protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…It has indeed been shown that the pancreas is dependent on eNampt and extracellular NMN for glucose-induced insulin secretion, which may partly explain why dysregulation of the circadian cycle affects glucose metabolism 32 . Indeed, metabolism 4749 , as well as aging 50, 51 , are known to be under the influence of the circadian rhythm, which further supports their connection to NAD + world and sirtuins. The brain, which centrally regulates metabolism via Sirt1, is also deficient in iNampt, however, there is no direct evidence yet of how essential circulating NMN is for it function.…”
Section: Pyridine Nucleotides and The Regulation Of Sirtuins’ Activitymentioning
confidence: 77%
“…It has indeed been shown that the pancreas is dependent on eNampt and extracellular NMN for glucose-induced insulin secretion, which may partly explain why dysregulation of the circadian cycle affects glucose metabolism 32 . Indeed, metabolism 4749 , as well as aging 50, 51 , are known to be under the influence of the circadian rhythm, which further supports their connection to NAD + world and sirtuins. The brain, which centrally regulates metabolism via Sirt1, is also deficient in iNampt, however, there is no direct evidence yet of how essential circulating NMN is for it function.…”
Section: Pyridine Nucleotides and The Regulation Of Sirtuins’ Activitymentioning
confidence: 77%
“…Interestingly, time-of-day-dependent rhythms in glycogen levels persist in fasted rodents (albeit at lower amplitude), suggesting that these rhythms are not simply secondary to feeding/fasting cycles (Ishikawa and Shimazu 1976). Not only do glycogen levels oscillate over the course of the day, but so do the activities of key glycogen metabolism enzymes; glycogen synthase displays maximum levels during the dark (active) phase in rodents, whereas glycogen phosphorylase peaks towards the end of the light (sleep) phase (Ishikawa and Shimazu 1980; Peret, et al 1976). Evidence in support of circadian clock involvement in mediation of these oscillations comes from recent studies by Doi et al, which report diminished oscillations in both hepatic glycogen levels and glycogen synthase expression/activity in Clock Δ19 mutant mice (Doi, et al 2010).…”
Section: Circadian Clock Control Of Metabolismmentioning
confidence: 99%
“…In contrast, there is increased activity of insulin and insulin-sensitive enzymes if the protein is consumed at the end of the night. 119,120 The above data suggest that protein turnover is a function both of the time of protein ingestion and of the other nonprotein components. While this has been demonstrated in liver, there is lack of data on the metabolic interrelationships of protein, amino acids, and dietary factors in muscle.…”
Section: Circadian Rhythms In Protein Turnovermentioning
confidence: 88%